Unravelling agronomic performance and genetic diversity of newly developed maize inbred lines for arid conditions - Abdallah A. Hassanin; Areej S. Jalal; Ehab M. Mahdy; Hend Mandour; Elsayed Mansour; Mohamed M. Kamara; Mohammed O. Alshaharni; Eman Fayad; Mohammed Alqurashi; Maha Aljabri; Thorya Abdulrahman Fallatah; Diaa Abd El-Moneim; et al. (PeerJ, 2025)
Investigating genetic diversity of maize inbred lines is crucial for enhancing breeding for higher yields, resilience, and ensuring sustainable maize production amidst climate change and the rapidly growing global population. This study aimed to evaluate the phenological attributes, plant stature, ear characteristics, and grain yield of 14 newly developed Egyptian maize inbred lines across three growing seasons under arid conditions in Egypt. Furthermore, the assessment of the genetic diversity among these lines using three molecular marker techniques: start codon targeted (SCoT), conserved DNA-derived polymorphism (CDDP), sequence-related amplified polymorphism (SRAP). Field evaluation revealed considerable variations in phenological characters including days to tasseling and silking. The earliest maturing lines such as IKA22 demonstrate potential suitability for short growing seasons. Plant and ear heights varied considerably. Taller lines (such as LCM54 and RA28C) potentially offered greater photosynthetic capacity, while shorter lines (such as IKA22, B17AB, and SSK36) may have exhibited improved lodging resistance, especially under adverse weather conditions. Ear diameter and length fluctuated across seasons, with ZBM40A, RA28C, DKCA2, and LZAM7B exhibiting favorable ear length and diameter. The number of rows per ear and kernels per row varied across seasons, with LZAM7B, RA28C and ZBM40A demonstrating the best performance. Grain yield per plant also revealed seasonal variation, with RA28C, ZBM40A, DKCA2, and LZAM7B showing higher yields. The assessed lines were grouped into six categories based on yield-related traits with RA28C demonstrating the best overall performance, followed by ZBM40A, DKCA2, and LZAM7B. Principal component analysis (PCA) identified associations between these lines and yield-related traits, emphasizing their potential as the most promising candidates for improving maize yield. Moreover, heatmap clustering confirmed the genetic potential and divergence of these lines. PCA demonstrated robust associations between grain yield and critical traits such as rows per ear, ear diameter, and kernels per row, emphasizing their importance for indirect selection. Molecular analysis amplified a total of 95 loci, of which 74 were polymorphic, reflecting substantial genetic variability. The percentage of polymorphism ranged from 0% to 100%, averaging 72.46%. Genetic distance analysis revealed a range of similarities and dissimilarities among these lines. The closest genetic similarity was observed between LZAM7B and ZBM40A, while the greatest divergence was found between LZAM7B and DKCA2. These findings offer valuable insights into the genetic potential of the studied inbred lines, laying a strong foundation for developing resilient, high-yielding maize hybrids for arid and semi-arid environments. Integrating phenotypic and molecular data provides valuable insights for selecting suitable inbred lines in hybrid maize breeding.